(untitled) (Eurasian Scientific Herald, 2022)
This article discusses proposals and recommendations for increasing the duration of nitriding to obtain a layer thickness by studying the composition and structure of steel and contrast materials using vacuum-ion-plasma coating methods when restoring details of working surfaces.